Computed tomography provides a “one-stop-shop” targeted analysis for coronary artery calcification and osteoporosis: a review - Luo, Jing; Wang, Qian; Liu, Wenhong; Liao, Huazhi; Qing, Weipeng; Zhang, Minyi; Tang, Deqiu; Luo, Guanghua; Zhao, Heng (Frontiers in Endocrinology, 2025)
The global trend towards longer lifespans has led to an aging population and a rise in the prevalence of diseases that predominantly affect elderly people. Coronary artery calcification (CAC) and osteoporosis (OP) are common in elderly populations. CT scans provide a reliable method to assess and monitor the progression of these diseases. In this review, the relationship between OP and CAC in terms of pathophysiological mechanism, comorbidity risk factors and clinical manifestations is reviewed, with a focus on the advancements in CT imaging, clinical applications and the possibility for “one-stop-shop” for examination.